Flavor of arabica coffee grown in Gayo Palteau as affected by varieties and processing techniques - Yusya Abubakar; Abubakar Karim; Fachrizal Fahlufi (Syiah Kuala University, 2011)
Coffee (Coffea sp) is one of the most popular drinks in Indonesia, as well as in the world. Coffee plantation has been grown in several areas in Indonesia, including Aceh province, and has become one of the most important plantation products with promising economic value. Both Arabica and Robusta are found in Aceh, however Arabica coffee grown more in the area because of its popularity in International market. This popularity is related to Arabica coffee distinctive flavor and aroma. To grow well, Arabica coffee requires land with altitude 1000 m or more above sea level. Therefore, in Aceh, it is grown in the Gayo Plateau with total area more than 90.000 hectares. As International market requires higher standard coffee, there is a need to provide a better quality coffee with a better taste, flavor and aroma. Several coffee varieties have been cultivated in the area for a long time, however the relation between variety and taste flavor has not been fully investigated. Other factors that may affect the taste, flavor and aroma is processing technique applied during postharvest and handling. Both wet hulling and dry hulling are practiced by small holders and farmers in the area. This study is aimed to investigate taste and flavor of Arabica coffee as affected by varieties and processing technique. The already grown varieties used in this study were Ateng Super (V1), Bergendal (V2), Bor-Bor (V3), Tim-Tim (V4) and Lini_S (V5). The processing techniques to be considered were Dry Hulling (TA) and Wet Hulling (TB). Observations to be recorded were organoleptic test (fragrance, acidity, body, flavor, aftertaste, balance), pH analysis and caffeine content. The result shows that the Tim-Tim variety get the highest organoleptic score, while between the two techniques, wet hulling provide a better acceptance from the panelist (get higher organoleptic scores)